ANALISIS KEEKONOMIAN PENGOPERASIAN ALAT PERONTOK UNTUK KEDELAI (STUDI KASUS: KECAMATAN MAJALENGKA, KABUPATEN MAJALENGKA) - Novi Dewi Sartika; Sutrisno Sutrisno; Emmy Darmawati (Fakultas Teknologi Pangan & Agroindustri (Fatepa) Universitas Mataram dan Perhimpunan Teknik Pertanian (PERTETA), 2018)
Majalengka is one of the regency that had been implemented the multipurpose threshers for soybean. The multipurpose thresher related with business sustainability in the region, so an economic analysis need to be done. The objective of this study was to assess the economics of multipurpose threshers in order to improve postharvest activity by using this multipurpose thresher. This research was conducted by operating two type of multipurpose threshers in the Sindang Kasih village as main soybean seed producing center. Thresher testing was done by setting the rotary cylinders speed on 515-570 rpm and 580-650 rpm. Weight losses of threshing operation was found 0.68-3.1%. The results of analysis for main operational cost was Rp. 327 - Rp. 369/kg, and BEP was reached at 15.7-19.2 ha/year that equal with 23,562 – 28,852 kg of soybean seeds/year or Rp. 9,604,100 - Rp. 11,540,649/year. The equipment rent cost of Rp. 400/kg was feasible with NPV Rp. 1,997,037 - Rp. 6,523,947, IRR 19.63-32.42% and net B/C of 1.11-1.43. An availability of soybean to be threshed was found during two periods of planting, namely 40 ha on February until April and 10 ha on June until August.